Cloud of cotton inside the maxillary sinus: A unique case report worth sharing - BHOWMICK, Ritoban; Gangopadhyay, Abhijit (Indian Journal of Case Reports, 2022)
The maxillary sinus is one of the most important structures present in the vicinity of the oral cavity. Unknowingly, it often gets involved when the environment of dentoalveolar structures of the maxillary unit jeopardize. There are lots of reasons such as trauma, forceful extraction which may change the internal environment of the maxillary sinus, and the balance of its microbial flora. Among them, oroantral communication and oroantral fistula cause chronic sinusitis inevitably. However, this case is unique by virtue due to the formation of chronic sinusitis by the intrusion of a foreign body by the patient himself and followed by the formation of an oroantral fistula after the extraction of an offending tooth.